A new theoretical framework for integration in freight transport chains. Issue 5 (3rd September 2019) - Reis, Vasco
ABSTRACT: At the European Union level, door-to-door freight transport chains – i.e. involving intermodal, combined, co modal or synchromodal transport – are seen as one solution for curbing the unsustainable growth of the transport sector. Integration is regarded as a key feature in the creation of enhanced transport chains. It would bring about purposeful coordination and alignment between transport agents with the aim of enhancing the performance of the transport service. However, integration also entails additional costs, so there are limits to its exploitation. Diverse theories and principles were used to study the dynamics of integration. System engineering principles were used to study the elements and structure of the transport chains; whereas logistics and supply chain principles were applied to explain agents' behaviouristic elements and performance elements. New institutional economics theory shed light on the types and problems of coordination, or on incentives to overcome the barriers. Network and graph theories are useful to characterise the structure of transport chains and networks. The literature review highlighted that less attention has been paid to both the identification of the fundamental components of integration and the understanding the role of integration on the performance of a transport chain. This paper proposes a novel conceptual framework by which to understand the nature and mechanisms of integration in freight transport chains. It makes use of the concept of fitness and takes into consideration insights derived from system engineering and transaction costs economics. The framework is made up of four interrelated Building Blocks (BB): the customer's demand requirements (BB1); the transport agents' profiles (BB2); the fitness (BB3); and the performance of the transport chain (BB4). Integration is the degree of matching (BB3) of selected components of the transport agents (BB2), chosen according to demand (BB1). The degree of matching will yield inefficiencies which will impact the performance (BB4) of the transport service. The framework identifies five dimensions of integration, corresponding to the various flows among agents, which are physical; logical; contractual; financial; and institutional. Finally, it considers three moments of integration: during production; while on recovery from a situation of non-compliance; and after the delivery of the goods. An initial validation assessment exercise was conducted with two case studies – one successful and one unsuccessful. This work complements others dedicated to understanding the organisation and production of transport chains. The framework can assist transport agents in identifying unexploited opportunities for enhancing integration or mitigating negative aspects. It can also support policy makers, for example, in efforts to prioritise investments in accordance with their potential impact on integration. Finally, as the framework provides details on how agents interact, it can support the development of freight transport models, particularly disaggregated approaches.